Workplace Empowerment of Nursing Professionals in Healthcare Industry - Rajalakshmi Ramu; B. V Kathyayani (Indian Journal of Psychiatric Nursing)
Background: Nurses have been called upon to lead and to be a partner in the transformation of healthcare Industry. Nurses and nurse managers must be empowered to perform their leadership roles to facilitate positive patient outcomes. Empowerment is possible when employees have access to information, support, resources, and the chance to discover and development. Aims and Objective: The aim was to investigate structural empowerment in nursing staff and to identify training needs to provide continuing education through workshop or conference. The objective of this study was to assess the level of empowerment of nurses working in hospital industry. Materials and Methods: A descriptive research design was adapted for the present study. A self-administrated questionnaire was distributed to the respondents on the basis of convenient sampling. Quantitative data were entered using SPSS version 17, and it was analyzed using descriptive statistics. Results: Majority of the respondents expressed that they empowered moderately. Conclusion: Empowerment of the nursing staff is very essential, and nursing administration must understand the importance of empowerment so that nursing professional can lead the hospitals effectively and facilitate the delivery of safe, high-quality patient care in hospitals.